Spatiality and Environmental Justice in Parkdale (Toronto) - Teelucksingh, Cheryl (Ethnologies, 2002)
RésuméAs part of the project to name environmental injustices in Canada, this article explores the significance of a critical analysis of social space to understand environmental justice problems in an urban Canadian community. Environmental injustices that impact on particular geographical locations have a readily apparent, fixed spatial aspect. However, I argue that a broader view to the politics of how space is produced and reproduced is necessary to explain the way in which the spatial manifestations of political economic transformations can create new and dynamic environmental injustices (Massey 1993). I at first outline some of the key components of the environmental justice perspective. Then, by drawing on critical work in the area of human geography, in particular Edward Soja’s (1996) and Henri Lefebvre’s (1991) work, I review the limitations of the dominant approach to spatiality in the American environmental justice literature. I then present my arguments in favour of a critical view to social space through a consideration of my field research findings in the Toronto community of Parkdale.